2018
DOI: 10.1002/1878-0261.12330
|View full text |Cite
|
Sign up to set email alerts
|

CPP‐E1A fusion peptides inhibit CtBP‐mediated transcriptional repression

Abstract: The carboxyl‐terminal binding proteins (CtBP) are transcriptional corepressors that regulate the expression of multiple epithelial‐specific and pro‐apoptotic genes. Overexpression of CtBP occurs in many human cancers where they promote the epithelial‐to‐mesenchymal transition, stem cell‐like features, and cell survival, while knockdown of CtBP in tumor cells results in p53‐independent apoptosis. CtBPs are recruited to their target genes by binding to a conserved PXDLS peptide motif present in multiple DNA‐bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 66 publications
4
26
0
Order By: Relevance
“…Immunoblot analysis was performed as described previously , and details are provided in supplementary material, Supplementary materials and methods.…”
Section: Methodsmentioning
confidence: 99%
“…Immunoblot analysis was performed as described previously , and details are provided in supplementary material, Supplementary materials and methods.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have demonstrated that CtBP acts as a transcriptional co-repressor, whereas quite a few studies have exposed context-specific of CtBPs in transcriptional activation [12]. For instance, CtBP2 has been shown to increase the expression level of Tiam1 in an NADH-dependent manner, and to activate the transcription factor 4 signaling pathway [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…The significance of the CtBP co-repressor composite in manifold developmental processes implies that the dysregulation of CtBPs expression in certain human tissues may be involved in oncogenesis [6]. Additionally, recent study implied that the CtBP protein was frequently hyper-activated in various types of tumor cells [12]. It is previously exposed that CtBPs comprise amino acid sequence homology with NADH-dependent dehydrogenases.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown previously that the Pep1-E1A peptide disrupts the interaction of CtBP1 with the PLDLS-containing repressor ZEB1 in cancer cells and relieves the transcriptional repression of CDH1 (E-cadherin) and BAX by the CtBPs (Blevins et al, 2018). To explore whether this peptide inhibitor can interfere with the transactivation function of CtBP1 and CtBP2, we preincubated Pep1-E1A with mouse primary microglia and astrocytes for 2 h prior to stimulation with LPS and measured mRNA levels of the above nine CtBP-regulated proinflammatory genes by RT-qPCR.…”
Section: Pep1-e1a Suppresses the Induction Of The Ctbp Target Genes Imentioning
confidence: 99%